Performativitet, æstetik, udsigelse: Lille note om det performatives æstetik - Kyndrup, Morten (Peripeti, 2024)
In this investigation into the notion and theories of performativity, especially as they have developed in Germany and Scandinavia over the last few years, Morten Kyndrup places performativity in a broader field of aesthetic theory and analysis in order to qualify its distinctive traits and possible resources for aesthetic thinking.